Association Between Minimum Inhibitory Concentration, Beta-lactamase Genes and Mortality for Patients Treated With Piperacillin/Tazobactam or Meropenem From the MERINO Study. (27th October 2020) - Henderson, A; Paterson, D L; Chatfield, M D; Tambyah, P A; Lye, D C; De, P P; Lin, R T P; Chew, K L; Yin, M; Lee, T H; Yilmaz, M; Cakmak, R; et al.
Abstract: Introduction: This study aims to assess the association of piperacillin/tazobactam and meropenem minimum inhibitory concentration (MIC) and beta-lactam resistance genes with mortality in the MERINO trial. Methods: Blood culture isolates from enrolled patients were tested by broth microdilution and whole genome sequencing at a central laboratory. Multivariate logistic regression was performed to account for confounders. Absolute risk increase for 30-day mortality between treatment groups was calculated for the primary analysis (PA) and the microbiologic assessable (MA) populations. Results: In total, 320 isolates from 379 enrolled patients were available with susceptibility to piperacillin/tazobactam 94% and meropenem 100%. The piperacillin/tazobactam nonsusceptible breakpoint (MIC >16 mg/L) best predicted 30-day mortality after accounting for confounders (odds ratio 14.9, 95% confidence interval [CI] 2.8–87.2). The absolute risk increase for 30-day mortality for patients treated with piperacillin/tazobactam compared with meropenem was 9% (95% CI 3%–15%) and 8% (95% CI 2%–15%) for the original PA population and the post hoc MA populations, which reduced to 5% (95% CI −1% to 10%) after excluding strains with piperacillin/tazobactam MIC values >16 mg/L. Isolates coharboring extended spectrum β-lactamase (ESBL) and OXA-1 genes were associated with elevated piperacillin/tazobactam MICs and the highest risk increase in 30-day mortality of 14% (95% CI 2%–28%). Conclusions: After excluding nonsusceptible strains, the 30-day mortality difference from the MERINO trial was less pronounced for piperacillin/tazobactam. Poor reliability in susceptibility testing performance for piperacillin/tazobactam and the high prevalence of OXA coharboring ESBLs suggests that meropenem remains the preferred choice for definitive treatment of ceftriaxone nonsusceptible Escherichia coli and Klebsiella . Abstract : Piperacillin/tazobactam should be avoided for ceftriaxone nonsusceptible Escherichia coli and Klebsiella spp. bloodstream infections, especially when minimum inhibitory concentrations are > 16 mg/L. Further assessment of current testing is warranted given disparity between commonly used methods and broth microdilution.